Methods for the early detection of drug-induced pancreatitis: a systematic review of the literature - Brian Hutton; David Moher; Becky Skidmore; Dianna Wolfe; Salmaan Kanji; Fatemeh Yazdi (BMJ Open)
Objectives We systematically reviewed the literature to identify evidence-informed recommendations regarding the detection of drug-induced pancreatitis (DIP) and, secondarily, to describe clinical processes for the diagnosis of DIP.Design Systematic review.Data sources Ovid MEDLINE, including Epub Ahead of Print, In-Process & Other Non-Indexed Citations, Embase Classic+Embase, the Cochrane Library.Eligibility criteria We included clinical practice guidelines, systematic reviews, narrative reviews and observational studies with a focus of establishing incidence, prevalence or diagnostic approaches for DIP. Clinical trials that diagnosed DIP as an outcome were also included.Data extraction and synthesis Two reviewers screened citations and performed data extraction. A narrative synthesis of the evidence was prepared.Results Fifty-nine studies were included. Early published evidence suggested serial pancreatic ultrasound could detect subclinical pancreatitis; however, subsequent studies demonstrated no utility of serial ultrasound or serial monitoring of pancreatic enzymes in the early detection of DIP. Two small studies conducted in patients with a high baseline risk of acute pancreatitis concluded serial monitoring of pancreatic enzymes may be useful to guide early discontinuation of medications with known associations with pancreatitis. Early discontinuation of medication was not advised for lower-risk patients because some medications cause transient elevations of pancreatic enzymes that do not progress to acute pancreatitis. Eight of 52 studies (15%) reporting a clinical diagnostic process for DIP reported using currently accepted criteria for the diagnosis of acute pancreatitis. A variety of methods were used to assess drug-related causality.Conclusions There is minimal evidence to support the use of serial monitoring by ultrasound or pancreatic enzymes to detect cases of DIP. Serial monitoring may be useful to guide early discontinuation of DIP-associated drugs in high-risk patients, but not in lower-risk patients. Greater uptake of standardised diagnostic and causality criteria for DIP is needed.Trial registration number CRD42017060473